Fiber-based modeling of in situ ankle ligaments with consideration of progressive failure. (16th August 2017) - Nie, Bingbing; Forman, Jason L.; Panzer, Matthew B.; Mait, Alexander R.; Donlon, John-Paul; Kent, Richard W.
Abstract: Ligament sprains account for a majority of injuries to the foot and ankle complex among athletic populations. The infeasibility of measuring the in situ response and load paths of individual ligaments has precluded a complete characterization of their mechanical behavior via experiment. In the present study a fiber-based modeling approach of in situ ankle ligaments was developed and validated for determining the heterogeneous force-elongation characteristics and the consequent injury patterns. Nine major ankle ligaments were modeled as bundles of discrete elements, corresponding functionally to the structure of collagen fibers. To incorporate the progressive nature of ligamentous injury, the limit strain at the occurrence of fiber failure was described by a distribution function ranging from 12% to 18% along the width of the insertion site. The model was validated by comparing the structural kinetic and kinematic response obtained experimentally and computationally under well-controlled foot rotations. The simulation results replicated the 6 degree-of-freedom bony motion and ligamentous injuries and, by implication, the in situ deformations of the ligaments. Gross stiffness of the whole ligament derived from the fibers was comparable to existing experimental data. The present modeling approach provides a biomechanically realistic, interpretable and computationally efficient way to characterize the in situ ligament slack, sequential and heterogeneous uncrimping of collagen fascicles and failure propagation as the external load is applied. Applications of this model include functional ankle joint mechanics, injury prevention and countermeasure design for athletes.